Perancangan Buku Ilustrasi Pop Up Candi Hindu-Budha Di Jawa Tengah Sebagai Media Edukasi Alternatif (Studi Kasus pada Anak Kelas V Sekolah Dasar Negeri 159 Sekejati Bandung) - Ricki Natali Jaya; Citra Kemala Putri; Sophia Purbasari (Universitas Informatika dan Bisnis Indonesia, 2019)
The knowledge of history is the study of incidents in the past. Therefore, the knowledge of history has many benefits, including: history can create a better future by taking lessons and experiences from the past. History can be studied if there are forms of heritage, such as a temples. The center of the temple in Indonesia is located in Central Java, the center of the Hindu-Buddhist temple. This region has the Borobudur Temple, which is best known by the people of Indonesia and foreign tourists, because Borobudur Temple is the largest Buddhist temple in the world. But many other temples are interesting to be known by the community, especially by elementary school children who start studying history in fifth grade elementary school. Learning history in schools requires a variety of learning methods, so that students are enthusiastic and do not get bored while learning in class. In overcoming the history of learning methods that are less diverse in fifth grade elementary school children in Bandung, pop-up books were chosen as a solution to this problem because, the use of pop-up book media is a new experience for many students at school. Data collection techniques carried out by interview and observation using mixed methods. The main media is a pop up book entitled